Mengukur Faktor Yang Memengaruhi Kesejahteraan Masyarakat Kabupaten/Kota Di Sulawesi Selatan Melalui Pendekatan Model Regresi Logistik - Rahman, Abdul (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
This study aims to measure community welfare at the district/city level in South Sulawesi Province using a binary logistic regression model approach. The research employs a quantitative method. The dependent variable is community welfare, measured by the Human Development Index (HDI), which is categorized into two groups (HDI < 71 and HDI ≥ 71). The independent variables include access to improved sanitation (SL), economic growth (PE), poverty (POV), and the open unemployment rate (TPT). The data used are secondary data obtained from the latest publications by the Central Statistics Agency (BPS). The analysis model used is binary logistic regression with the Maximum Likelihood Estimation (MLE) method. The results show that improved sanitation (SL) has a positive and significant effect on community welfare, economic growth (PE) has a significant negative effect, and the open unemployment rate (TPT) has a significant positive effect, while poverty (POV) does not have a significant effect on community welfare. These findings highlight the importance of strengthening basic infrastructure such as sanitation, transforming economic growth policies to be more inclusive, and creating productive employment opportunities in order to improve community welfare at the local level.